Systematic studies of Scleractinian fauna of the Philippines - Nemenzo, Francisco 1935 (Quezon City Natural and Applied Science Bulletin, 1955)
On the scleractinian fauna of Puerto Galera Bay, Oriental Mindoro and Laguimano Bay, Quezon.contents: I. Suborder FungiidaII. Faviida III. Caryophylliida IV. Dendrophylliida V. Suborder Astrocoeniida (Part) VI. Suborder (Montipora and Acropora) Part 1. Text and Part 2 Plates VII. additional forms
Keywords: Coelenterates; Scleractinian fauna; Corals